2003
DOI: 10.1189/jlb.0702361
|View full text |Cite
|
Sign up to set email alerts
|

Telomere shortening in leukocyte subpopulations from baboons

Abstract: To address questions about telomere length regulation in nonhuman primates, we studied the telomere length in subpopulations of leukocytes from the peripheral blood of baboons aged 0.2-26.5 years. Telomere length in granulocytes, B cells, and subpopulations of T cells all decreased with age. Overall, telomere length kinetics were lineage- and cell subset-specific. T cells showed the most pronounced, overall decline in telomere length. Levels of telomerase in stimulated T cells from old animals were lower than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
23
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 53 publications
7
23
1
Order By: Relevance
“…A similar rate of shortening is seen in PBMCs from chimpanzees (Feng et al 1999), and these rates are similar to that seen in humans. Telomere shortening also occurs with age (between 0.2 and 26.5 years) in leukocytes of baboons (Papio hamadryas cynocephalus), and in general, cell type-specific telomere kinetics in baboons are remarkably similar to those observed in humans (Baerlocher et al 2003).…”
Section: Primatesmentioning
confidence: 81%
“…A similar rate of shortening is seen in PBMCs from chimpanzees (Feng et al 1999), and these rates are similar to that seen in humans. Telomere shortening also occurs with age (between 0.2 and 26.5 years) in leukocytes of baboons (Papio hamadryas cynocephalus), and in general, cell type-specific telomere kinetics in baboons are remarkably similar to those observed in humans (Baerlocher et al 2003).…”
Section: Primatesmentioning
confidence: 81%
“…Granulocyte telomere lengths were measured for 132 baboons aged between 0.92 and 24 years. 25 Granulocytes were used because they are readily obtained and purified to homogeneity and are short-lived (circulation life spans, Ͻ 5-10 hours).…”
Section: Telomere-length Datamentioning
confidence: 99%
“…Granulocyte telomere lengths were measured for 132 baboons aged between 0.92 and 24 years. 25 Granulocytes were used because they are readily obtained and purified to homogeneity and are short-lived (circulation life spans, Ͻ 5-10 hours).T-cell culturing and computational techniques for 5 rhesus macaques (2-9 measurements per animal) were identical to those of baboons. 36 Total white blood cell telomere lengths were measured for 14 rhesus macaques aged between 2.8 and 15.3 years.…”
mentioning
confidence: 99%
“…Interestingly, similar kinetics of telomere shortening were observed over the age range of 0.2-26.5 years in baboons. 89 Recently, by using stochastic simulation of replication rates of HSC in vivo based on telomere length kinetics, Shepherd et al 90 demonstrated that HSC turnover rates differ quite substantially between vertebrates, ranging from once per 2.5 weeks in mice to once per 8-10 weeks in cats to once per 45 weeks in humans.…”
Section: Kinetics Of Telomere Shortening In Sub-populations Of Human mentioning
confidence: 99%